The impact of implementing devolution on citizen participation and service provision in Sunningdale, Harare, Zimbabwe - Shumba, Precious; Gutsa, Ignatius (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this paper we examine how devolution, as mandated by Zimbabwe’s 2013 Constitution, affects local governance, focusing on citizen participation and service delivery in Ward 10 of Sunningdale, Harare. Although devolution is enshrined in the Zimbabwean constitution, the actual implementation has been fraught with inconsistencies between policy and practice. Centralized decision-making has hindered local authorities from fully exercising their powers, limiting citizen engagement in governance and effective service provision. In this study we utilised an interpretive methodological approach to collect data through semi-structured interviews and online focus group discussions with local government officials, experts, and Sunningdale residents. The findings reveal a mixed understanding of devolution among residents, with most lacking access to information about its implications. Though residents expressed hope that devolution could improve services such as water provision and housing, political and institutional challenges continue to undermine its effective implementation. Local government experts suggest that successful devolution in Zimbabwe requires empowering local authorities with greater financial control and decision-making autonomy. The study highlights the importance of education and awareness programmes to enhance citizen understanding of devolution, as well as the need for a clear legislative framework to support the decentralization process. We conclude that while devolution holds promise for improving governance and service delivery, its success depends on political will, institutional capacity, and genuine citizen engagement.